Rnf32 is not essential for spermatogenesis and male fertility in mice - Hao Kong; Yufeng Yin; Ni Zeng; Yunfei Zhu; Yiqiang Cui (PeerJ)
Background Ring finger motifs are found in a variety of proteins with diverse functions, often involved in protein-DNA or protein–protein interactions. The Rnf32-encoded protein contains two such motifs and is predominantly expressed in the testes and ovaries, suggesting that its expression may be regulated by elements within the Rnf32 promoter region. Rnf32 is active during spermatogenesis, mainly in spermatocytes and spermatids, indicating a potential role in sperm development. Methods We established an Rnf32 knockout (Rnf32−/−) mouse model using CRISPR/Cas9 technology. Gene expression was analyzed via reverse transcription quantitative polymerase chain reaction (RT-qPCR). Testicular and epididymal phenotypes were assessed through histological and immunofluorescence staining, and fertility and sperm motility were evaluated. Results Here, we successfully established an Rnf32 knockout mouse model using CRISPR/Cas9 technology. Surprisingly, male Rnf32−/− mice exhibited normal fertility, with no significant differences in testicular and epididymal histology, spermatogenesis, sperm count, or motility compared to Rnf32+/+ mice. These findings suggest that Rnf32 may not be essential for male fertility in mice, and its potential functions warrant further investigation.